PAVING THE WAY FOR UMKM SUCCESS: A SERVICE INITIATIVE FOR THE WELFARE OF RURAL COMMUNITIES - Irfansyah Irfansyah (JOURNAL OF COMMUNITY DEDICATION, 2022)
The importance of service to rural communities in improving welfare through the development of micro, small and medium enterprises (MSMEs). Service in the form of skills training, access to capital, and opening new markets allows village MSMEs to grow and develop, creating jobs and reducing poverty. In addition, the health programmes provided help improve the quality of life for villagers. Free health counselling and check-ups facilitate access to medical services, which has positive implications for economic productivity. Furthermore, this service strengthens social ties and solidarity among villagers, building active participation in village development activities. As such, the service to the village community provides comprehensive economic, social and health impacts, and creates a foundation for long-term prosperity and sustainable development.